Hand hanger / Muhamad Firdaus Muhamad Izhar - Muhamad Izhar, Muhamad Firdaus (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Hand hanger is designed to assist special education students in daily life by helping them pick up items with their left hand. This product is designed with a minimalist concept and designed to be easy to carry and use for them.